2019
DOI: 10.3390/biology8040092
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antidiabetic, Anti-Obesity and Antioxidant Analysis of Ocimum basilicum Aerial Biomass and in Silico Molecular Docking Simulations with Alpha-Amylase and Lipase Enzymes

Abstract: The present study explored phytochemicals, porcine pancreatic α-amylase (PPA) and lipase (PPL) inhibitory activities and antioxidant potential of polar and nonpolar extracts of the leaves and flowers of Ocimum basilicum and the in-silico mode of interaction between these enzymes and the major chemical constituents of the herb. The hexane extract (HE) and hydro-ethanolic extract (EE) obtained sequentially were used to estimate PPA and PPL inhibitory and antioxidant activities, total phenolic content (TPC) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 49 publications
3
22
0
1
Order By: Relevance
“…In many studies, basil essential oil was shown to act as an antidiabetic, anti-obesity, and anti-Alzheimer's agent [14,20]. There are many investigations confirming that such compounds of essential oils as eugenol, linalool, 1,8-cineole, and β-pinene (present in basil essential oil analyzed in the present study) possess many biological activities connected with anti-diabetic and neuroprotective action [12,21].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In many studies, basil essential oil was shown to act as an antidiabetic, anti-obesity, and anti-Alzheimer's agent [14,20]. There are many investigations confirming that such compounds of essential oils as eugenol, linalool, 1,8-cineole, and β-pinene (present in basil essential oil analyzed in the present study) possess many biological activities connected with anti-diabetic and neuroprotective action [12,21].…”
Section: Introductionsupporting
confidence: 63%
“…However, the correlation analysis confirmed only a moderate positive correlation between the anti-α-amylase activity and the linalool content in the essential oils tested, R 2 = 0.44 (data not published). The in vitro antidiabetic and anti-obesity properties of basil essential oils were also confirmed in a study conducted by Noor et al [20]. Their ability to suppress endogenous glucose release was found to contribute to the inhibition of glycogenolysis and/or stimulation of glycogenesis.…”
Section: Discussionmentioning
confidence: 56%
“…All of the crystalline compounds were detached from the RBD structure prior to docking. The RBD structure was prepared using AutoDock tools [ 39 , 42 ]. Gassteiger charges were optimized and Polar hydrogens were added.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of pancreatic lipase shown by plant extracts was likely ought to presence of secondary metabolites. The structural features of secondary metabolites or phytochemicals have the ability to bind with the amino acid residues of proteins to restrict their functions [29]. The pancreatic lipase is a potential pharmacological target to control obesity and does not involved complex mechanism of operation.…”
Section: Antioxidant Activity and Pancreatic Lipase Inhibition Assaymentioning
confidence: 99%